PERENCANAAN STRUKTUR BANGUNAN GEDUNG ASRAMA HAJI SEMARANG - Fajar Rizkiyawan; Bambang Triyanto; Hartopo Hartopo; Totok Apriyanto (Jurnal Teknik Indonesia, 2023)
Planning the Structure of the Semarang Hajj Dormitory Building is located on Jl. Abdul Rahman Saleh No. 285, Kalipancur, Kec. Ngaliyan, Semarang City, Central Java. This arama was built to improve the facilities and infrastructure of pilgrims in the Semarang area.The planning of this building is carried out with primary data such as data from soil sondir, and is equipped with other secondary data. This structural planning analysis is assisted by the SAP 2000 software application (Structure Analyst Program) for structural modeling and calculating internal forces. The analysis carried out includes: calculation of the structure of the Foundation, Columns, Beams, Plates and Roofs.From the results of the analysis obtained the type of foundation using piles with P1:1.00x1.75x0.70 m with 2 piles measuring 30x30 cm 9 m depth, P2:1.80x1.80x0.70 m with 4 piles measuring 35x35 cm depth 9 m, P3:1,90x1,90x0,70 m with 5 piles measuring 30x30 cm with a depth of 9 m. beam size 40x70 3-D22 principal reinforcement (support) 10-150 shear reinforcement, 3-D22 principal reinforcement (field) 10-150 shear reinforcement. beam size 30x50 2-D22 principal reinforcement (support) 10-150 shear reinforcement, 2-D22 main reinforcement (field) 10-150 shear reinforcement. beam size 15x30 main reinforcement 2-D19 (support) shear reinforcement 10-150, 2-D19 main reinforcement (field) shear reinforcement 10-150. Column 60x60 main reinforcement 8-D25, shear reinforcement 10-150. Column 70x70 main reinforcement 12-D25, shear reinforcement 10-150. Roof rafter beam WF 250.125.6.9, steel column WF 250.125.6.9, gording C. 125.50.20.2,3, roof covering: steel roof (span deck) distance between roof rafter beams 4 m, distance between steel columns 4 m, distance between gording 1 m, bolt diameter using 16 mm and steel anchor diameter 16 mm (length 50 cm). From the calculation results, each element of the building structure can be categorized as safe.